2020
DOI: 10.1093/ndt/gfaa261
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19-related mortality in kidney transplant and dialysis patients: results of the ERACODA collaboration

Abstract: Background. Patients on kidney replacement therapy comprise a vulnerable population and may be at increased risk of death from coronavirus disease 2019 (COVID-19). Currently, only limited data are available on outcomes in this patient population. Methods. We set up the ERACODA (European Renal Association COVID-19 Database) database, which is specifically designed to prospectively collect detailed data on kidney transplant and dialysis patients with COVID-19. For this analysis, patients were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
389
2
23

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 357 publications
(443 citation statements)
references
References 21 publications
29
389
2
23
Order By: Relevance
“…Importantly, in all dialysis and general population's COVID-19 studies, the most consistent demographic risk factor for death was age. Our study con rmed the signi cant association of older age and death, which is also aligned with the ndings of the European ERACODA study [24]. Age was also identi ed as a risk factor for higher mortality in studies from the UK Renal Registry, from Japan and Spain [16,15,22].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Importantly, in all dialysis and general population's COVID-19 studies, the most consistent demographic risk factor for death was age. Our study con rmed the signi cant association of older age and death, which is also aligned with the ndings of the European ERACODA study [24]. Age was also identi ed as a risk factor for higher mortality in studies from the UK Renal Registry, from Japan and Spain [16,15,22].…”
Section: Discussionsupporting
confidence: 88%
“…reported by the ERACODA study of 26 European and North Mediterranean countries including 768 dialysis patients [24]. To our knowledge, this is the rst study that evaluates the number of comorbidities or multimorbidities as a risk factor for death in hemodialysis patients with COVID-19.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mortality risk was 1.28 (95% CI 1.02–1.60) times higher in transplant recipients compared with age- and sex-matched dialysis patients. In both groups, mortality is in large part related to age and in dialysis patients also to frailty status [ 23 ]. In addition, frequent hospital attendance, as is needed for in-centre dialysis, may increase the risk of infection for end-stage kidney disease patients [ 24 ].…”
Section: Ckd Is the Disease Condition Conveying The Highest Risk Formentioning
confidence: 99%
“…Emerging data revealed risk factors for severe COVID-19 among patients on kidney replacement therapy. The European Renal Association COVID-19 Database (ERACODA) cohort, established by the ERA-EDTA, showed that within dialysis and kidney transplant populations the risk conferred by classical risk factors for severe COVID-19 is completely different than in the general population [ 23 ]. For instance, in dialysis patients with COVID-19 [ n = 768, of which 192 (25%) died], the relative contribution of age to mortality is considerably less than in subjects from the general population.…”
Section: End-stage Kidney Disease and The Need For Specific Studiesmentioning
confidence: 99%